Effects of advanced glycation end-products on the proliferation and differentiation of osteoblast-like cells - McCarthy, Antonio Desmond (1997)
Two different lines of osteoblast-like cells were used to investigate the effect of advanced glycation end-products of bovine serum albumin on cell proliferation and differentiation. These parameters were found to be both dose- and time-dependent. Cell proliferation remained unchanged after a 24 h incubation period, it increased after intermediate periods of incubation with advanced glycation end-products, but was found to be depressed after several days incubation. Cellular alkaline phosphatase activity followed a similar pattern: an initial increase induced by advanced glycation end-products was generally followed, after relatively long incubation periods, by a slight but significant decrease in this parameter. 45Ca2+ uptake was only significantly inhibited by advanced glycation end-products after 24 h incubation. These results suggest that advanced glycation end-products directly regulate osteoblast proliferation and differentiation in a dose and time dependent manner.